(untitled) (Physical Education, Health and Social Sciences, 2025)
Background: Compassion is a core aspect of nursing practice that affects nurse-patient relationships as well as outcomes of care. Although it is central to the practice, the term is often used interchangeably with other conceptually similar terms like empathy or caring. Aim: This article critiques the concept of compassion in nursing Applying Walker and Avant’s framework to make its defining characteristics, antecedents, and consequences clear and to investigate its theoretical and practical implications. Methods: Systematic concept analysis was carried out based on nursing and interdisciplinary literature using Walker and Avant’s eight-step process. Jean Watson’s Theory of Human Caring was employed to contextualize the theoretical implications of compassion. Results: Five defining characteristics were found: empathy, relational understanding, intentionality, presence, and action-oriented care. The identification of suffering was a main antecedent, while improved therapeutic relationships and patient satisfaction were core consequences. Constructed cases demonstrated the real-world application and lack of compassion. Conclusion: Compassion in nursing goes beyond an affective response; it is a deliberate, relational, and executable commitment to easing suffering. It is essential to holistic and ethical nursing practice and is highly consonant with Watson’s theory.